A case of gastric cancer after sleeve gastrectomy. Issue 4 (10th December 2019) - Yamashita, Takeshi; Tan, Jeremy; Lim, Eugene; Eng, Alvin; Ong, Hock S; Chan, Weng H
Abstract: There is concern over how to survey the remnant upper gastrointestinal tract, as well as what to do if a patient subsequently develops an upper gastrointestinal cancer following bariatric surgery. We hereby report a case of gastric cancer arising 8 years after a laparoscopic sleeve gastrectomy (LSG). The patient, a 42 year‐old woman, was diagnosed with a gastric cancer via esophagogastroduodenoscopy (EGD). As such, she underwent a laparoscopic total gastrectomy with lymphadenectomy. The final histopathology was that of a poorly differentiated adenocarcinoma with signet‐ring cells without lymph node metastases (staging pT4aN0). The background gastric mucosa displayed no Helicobacter pylori . There have only been a few reported cases of gastric cancer after sleeve gastrectomy. Nevertheless, it may be wise to consider performing EGD at regular intervals after bariatric surgery, especially in Asia. In this regard, LSG holds an advantage over Roux‐en‐Y gastric bypass with respect to the feasibility of surveillance of the remnant stomach.